2015
DOI: 10.1080/11263504.2015.1095253
|View full text |Cite
|
Sign up to set email alerts
|

The MAES process in Italy: Contribution of vegetation science to implementation of European Biodiversity Strategy to 2020

Abstract: Target 2 of the European Biodiversity Strategy to 2020, whose aim was to maintain and restore ecosystems and their\ud services, deals in practical terms with the mapping and assessment of ecosystems and their services, with the development\ud of green infrastructure and with halting the loss of biodiversity at the EU, national, and subnational levels. The aim of this\ud short communication was to show the activities currently being carried out in Italy that are related to this target, focusing\ud on the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The recommended actions that emerge from this study have been applied to pilot projects whose aim is to implement the GI strategy at the national level [18] and have been proposed at the European level within the context of the MAES Urban Pilot of the EU Commission [4]. Future research efforts will be made to fill the aforementioned existing gaps in knowledge, such as the need for a better definition of potential synergies and trade-offs between alternative urban forestry choices, a more comprehensive assessment of the complex cultural value of urban trees and forests, and a more in-depth investigation of the issue of ecological connectivity in urban contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended actions that emerge from this study have been applied to pilot projects whose aim is to implement the GI strategy at the national level [18] and have been proposed at the European level within the context of the MAES Urban Pilot of the EU Commission [4]. Future research efforts will be made to fill the aforementioned existing gaps in knowledge, such as the need for a better definition of potential synergies and trade-offs between alternative urban forestry choices, a more comprehensive assessment of the complex cultural value of urban trees and forests, and a more in-depth investigation of the issue of ecological connectivity in urban contexts.…”
Section: Discussionmentioning
confidence: 99%
“…As recently proposed for the implementation of the European Biodiversity Strategy for 2020 [17], actual vegetation cover can be considered as an effective operational proxy when outlining overall ecosystem complexity [18]. Concurrently, plant communities and plant species are widely recognized as being among the main providers of ES in urban areas, especially in the form of forests though also as isolated trees [19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…Both the areal and linear elements occurring in the landscape mosaic and dominated by woody species have been assumed as suitable habitats for oak persistence and dispersal, but their performance was supposed to be conditioned by the respective degree of naturalness. Specifically, naturalness has been assessed accounting for the physiognomic and structural features of the mapped woody elements with respect to those of the PNV [42] (step 1c, Figure 2; Supplementary Material Table S1): areal and linear elements dominated by nonnative species and/or with a regular structure due to plantation activities were considered less natural than those dominated by the native species typical of the PNV and showing a spontaneous cover pattern.…”
Section: Firstmentioning
confidence: 99%
“…This is the case for the VPL unit in the southeastern sector of the study area, where only a few and low-priority conservation nodes could be identified and only 2 of the 20 restoration links were designed. Such a result suggests that conservation and restoration priorities should be framed in the first place on the difference between actual and potential cover of natural ecosystems, and only secondarily on the spatial pattern of remnants, as already proposed for the assessment of ecosystem conservation status at the national and regional level [42]. As regards the adopted connectivity indicators and with respect to consolidated practice [45,75], an approach not just based on node importance and link removal function allowed the contribution made by further elements of the landscape mosaic to be enhanced.…”
Section: Strength and Weakness Of Prioritization Proceduresmentioning
confidence: 99%
“…Therefore, restoration/conservation actions were prioritised after the assessment of the respective ecosystem conservation status of such GI components. Criteria for the assessment were customised from those adopted for the implementation of the MAES process at the national level [70] and included:…”
Section: Step C-prioritisation Of Gi Restoration and Conservation Actmentioning
confidence: 99%